VARIATIONS IN GROWTH, YIELD, AND ANATOMY OF THREE VARIETIES OF SOYBEANS (GLYCINE MAX L. – FABACEAE) - Y. A. Al-Janabi; A. Ch. Al-Fahad; M. A. Al-Hadeethi; P. Sutthisaksopon; H. Kh. Rahman (مجلة الأنبار للعلوم الزراعية)
This study was conducted in the fields of Abu-Ghraib City in Baghdad during the summer of 2022 by applying a RCBD in a split-plate arrangement with three replications. The study included two factors, the first represented glutathione concentrations of 0, 75, 150, and 225 mg L-1, and the second included three soybean varieties (Giza 82, Giza 83, and Giza 35). The results showed that the 225 mg L-1 glutathione had significant positive efficacy on plant height, branches per plant, leaf area, pod numbers, seed number per pod, weight of 100 seeds, individual plant yield, glutathione content in leaves, SOD enzyme activity, vascular bundle thickness, and density of starchy matter stored in the pith (83.22 cm, 7.00 plant shoot-1, 23.77 dm2, 74.22 plants pod-1, 2.644 seed pod-1, 13.733 g, 31.9 g plant-1, 11.371 micromole g-1 fresh weight, 10.211 g-1 fresh weight). Also, while the Giza 82 variety was superior in leaf area and fertility percentage (23.07 cm2, 94.44%), the Giza 35 variety excelled in pod numbers, individual plant yields, glutathione percentage in the leaves, and SOD enzyme activity.